Genetic differentiation in two widespread, open-forest bird species of Southeast Asia (Copsychus saularis and Megalaima haemacephala): Insights from ecological niche modeling. Issue 5 (1st October 2015) - Lim, Haw Chuan; Zou, Fasheng; Sheldon, Frederick H.
Abstract: Ecological niche modeling has emerged as an useful tool in the investigation of the phylogeographic histories of species or communities in a region. The high biodiversity (oftentimes cryptic), and complex geography and geological history of Southeast Asia particularly call for multipronged approaches in phylogeographic investigations. Past studies have focused on taxa that are associated with lowland rainforests, which is the dominant natural vegetation type. Here, we combine published phylogenetic data, ecological niche modeling and paleo-climate models to reveal potential drivers of divergence in two open-forest bird species, the oriental magpie-robin Copsychus saularis and Coppersmith barbet Megalaima haemacephala . In spite of broad overlap in current distributions, there are subtle differences in their climatic niches, which result in different responses to past climatic changes. For C. saularis, both Last Glacial Maximum climate models indicated that the entire Sundaland was climatically suitable, while phylogenetic analyses found divergent eastern and western Sundaland lineages. We thus postulate that this genetic divergence was a result of past separations of coastal habitats into eastern and western portions due to the emergence of Sunda shelf as sea-level fell. The current separation of morphological subspecies in Borneo is maintained by low climatic suitability (high annual rainfall) in certain regions. The extirpation of M. haemacephala from Borneo and southern Malay Peninsula might have been driven by unsuitable conditions (high temperature seasonality) in central Sundaland and/or the lack of open woodlands. Our study shows that ecological niche modeling adds a powerful dimension to our attempt to understand lineage evolution in space.